Study the Effect of Various Parameters on the Synthesis of ZSM-5 Zeolite (Journal of Engineering, 2018)
ZSM-5 zeolite was synthesis under hydrothermal conditions at 175oC. The synthesis parameters have been investigated to find optimum synthesis method. Firstly, the crystallization time has been investigated to find the optimum crystallization time. Also, the ageing time was studied. The morphology, structure, and composition of the synthesized ZSM-5 zeolite were characterized using scanning electron microscopy (SEM), pH meter, viscometer, and X-ray powder diffraction (XRD). The bulk Si/Al ratio of ZSM-5 zeolite was in the range of 9.5—11.7. The synthesized ZSM-5 zeolite with appropriate ageing time could adjust crystal size and degree of the crystallinity. The crystal size of ZSM-5 zeolite obtained at an ageing time of 24 h was around 2.0 μm. The suitable aging time was 24 h, and the relative crystallinity of ZSM-5 zeolite could reach up to 100% after crystallization for 48 h at 175oC